Bacterial growth from the surgical wound base smear at the end of the operation and superficial surgical site infection in the administration of cefazolin single dose, ceftriaxone single dose, and ceftriaxone 3 days as prophylactic antibiotics in cases of - Mario Daniel Simatupang; I Wayan Suryanto Dusak; I Ketut Suyasa; I Gede Eka Wiratnaya (DiscoverSys Inc., 2021)
Background: The use of prophylactic antibiotics in hospitals still often found to be not in accordance with the guidelines of prophylactic antibiotics used and therapy published by the hospital itself. This study aims to compare the effectiveness of prophylactic antibiotics between cefazolin and ceftriaxone in single-dose administration in patients with closed long bone fractures after implant surgery in Sanglah General Hospital on the incidence of Surgical Site Infection (SSI) and germ growth on the base of the surgical wound.Methods: This study used a randomized clinical trial design from a population of closed long bone fracture patients who underwent implant surgery at Sanglah General Hospital. The sample selection was carried out by consecutive sampling during the period July-August 2020. The statistical test was the Chi-Square Test or Fisher Exact Test using the SPSS version 20 for Windows.Results It was found that there was no growth of germs, or in other words, negative culture results were obtained in all study subjects (growth of N (%) 0 (0%), p = -) bacteria in all three groups on a single dose and 3-days dose. SSI did not occur in all study subjects in the three groups so that it could automatically be concluded that there was no difference in the proportion of SSI incidents in the three groups (SSI incidence N (%) 0 (0%), p = -) on single-dose and 3 days dose antibiotics administration, so that the proportional comparison test, either the Chi-Square test or the Fisher Exact test, cannot be performed.Conclusion The prophylactic antibiotics (which are the cephalosporins, namely single dose generic cefazolin and single-dose generic ceftriaxone and 3 days dose) have the same effectiveness in preventing the growth of germs on the surgical wound base smear and prevent the occurrence of superficial SSI on the 30th postoperative day.